Towards a Technology-Enabled Framework for Community Healthcare: A Multi-Stakeholder Qualitative Assessment of Uganda's VHT Program - Mukalere, Justine; Ssembatya, Richard; Ejiri, Annabella Habinka (Journal of Information System and Informatics, 2025)
Community Health Worker (CHW) programs, like the VHT-Program in Uganda, play a critical role in bridging community-health system gaps, especially in resource-constrained areas. This study explored its implementation with a focus on data management, technological infrastructure, and governance, guided by the Health Metrix Network (HMN) framework. The aim was to examine the VHT-Program's implementation from a multi-stakeholder perspective in selected districts of Uganda, informing the design of a technology-enabled community health framework. A qualitative, cross-sectional design was used, gathering data through interviews and focus groups with 147 participants, including VHTs, health workers, district health officials, and community members from Kibuku, Bulambuli, and Bugweri districts. The analysis, using Braun & Clarke’s thematic method, revealed eight key themes: Health Information System Resources, Data Sources, Data Management, Leadership & Governance, Dissemination and Use, Coordinating Mechanisms, Connectivity, and Challenges & Solutions. While some HMN components were affirmed, gaps in data management, coordination, and infrastructure were identified. This informed the development of the JTM-HMN Framework, which proposes a context-specific, integrated approach to guide policy development and the implementation of technology-driven healthcare interventions.